2019
DOI: 10.33429/cjas.09218.4/6
|View full text |Cite
|
Sign up to set email alerts
|

On the Efficiency of Stock Markets: A Case of Selected OPEC Member Countries

Abstract: The study investigates the stock market efficiency of selected OPEC member countries within the context of random walk hypothesis and volatility approaches using monthly data on stock market indices from January, 2005 to April, 2016. Parametric (variance ratio: homoskedastic and heteroskedastic martingale), nonparametric (the Wright ranks and scores) tests and ARCHtype estimation are performed. Results of both parametric and nonparametric tests indicate that only Qatar's stock market is weak-form efficient. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…These findings imply that prices do not fully reflect the information available and that changes in prices are not independent and identically distributed. These findings are in line with the evidence suggested by the authors Atac and Tas (2019), Olubiyi and Olopade (2019), Mphoeng (2019) that show inefficiency, in its weak form, which allows investors to have abnormal gains without incurring increased risk. Source: Own elaboration…”
Section: Source: Own Elaborationsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings imply that prices do not fully reflect the information available and that changes in prices are not independent and identically distributed. These findings are in line with the evidence suggested by the authors Atac and Tas (2019), Olubiyi and Olopade (2019), Mphoeng (2019) that show inefficiency, in its weak form, which allows investors to have abnormal gains without incurring increased risk. Source: Own elaboration…”
Section: Source: Own Elaborationsupporting
confidence: 92%
“…Chaker and Sabah (2018) tested the efficiency, in their weak form, in the markets of the United Arad Emirates (UAE), Saudi Arabia, Oman, Kuwait and Bahrain, showing that none of the analysed markets follow the random walk hypothesis. Atac and Tas (2019), Olubiyi and Olopade (2019), Mphoeng (2019) examined the market efficiency, in its weak form. Atac and Tas (2019) investigated the Istanbul stock exchange, and have shown that the efficiency hypothesis is rejected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The premise for studying the OPEC member countries is justified for the fact that their economic performance has been linked to oil sector since they heavily depend on oil revenue. This is not farfetched looking at the share of oil exports in their total exports that fluctuates around 70 per cent, with average of 38 per cent contribution to their GDP for the past 10 years (Olubiyi and Olopade, 2018). Similarly, the low degree of financial development in these countries urges policy makers and researchers to consider the study of these countries as posited by Rad et al (2018).…”
Section: Introductionmentioning
confidence: 99%